Black porous silicon as a photothermal agent and immunoadjuvant for efficient antitumor immunotherapy. (15th October 2022) - Xu, Wujun; Pang, Cui; Song, Chaojun; Qian, Jing; Feola, Sara; Cerullo, Vincenzo; Fan, Li; Yu, Haijun; Lehto, Vesa-Pekka
Abstract: Photothermal therapy (PTT) in combination with other treatment modalities has shown great potential to activate immunotherapy against tumor metastasis. However, the nanoparticles (NPs) that generate PTT have served as the photothermal agent only. Moreover, researchers have widely utilized highly immunogenic tumor models to evaluate the immune response of these NPs thus giving over-optimistic results. In the present study black porous silicon (BPSi) NPs were developed to serve as both the photothermal agent and the adjuvant for PTT-based antitumor immunotherapy. We found that the poorly immunogenic tumor models such as B16 are more valid to evaluate NP-based immunotherapy than the widely used immunogenic models such as CT26. Based on the B16 cancer model, a cocktail regimen was developed that combined BPSi-based PTT with doxorubicin (DOX) and cytosine-phosphate-guanosine (CpG). BPSi-based PTT was an important trigger to activate the specific immunotherapy to inhibit tumor growth by featuring the selective upregulation of TNF-α. Either by adding a low dose DOX or by prolonging the laser heating time, a similar efficacy of immunotherapy was evoked to inhibit tumor growth. Moreover, BPSi acted as a co-adjuvant for CpG to significantly boost the immunotherapy. The present study demonstrates that the BPSi-based regimen is a potent and safe antitumor immunotherapy modality. Moreover, our study highlighted that tuning the laser heating parameters of PTT is an alternative to the toxic cytostatic to evoke immunotherapy, paving the way to optimize the PTT-based combination therapy for enhanced efficacy and decreased side effects. Statement of significance: Tumor metastasis causes directly or indirectly more than 90% of cancer deaths. Combination of photothermal therapy (PTT), chemotherapy and immunotherapy based on nanoparticles (NPs) has shown great potential to inhibit distant and metastatic tumors. However, these NPs typically act only as photothermal agents and many of them have been evaluated with immunogenic tumor models. The present study developed black porous silicon working as both the photothermal conversion agent and the immunoadjuvant to inhibit distant tumor. It was recognized that the poorly immunogenic tumor model B16 is more appropriate to evaluate immunotherapy than the widely used immunogenic model CT26. The coordination mechanism of the PTT-based combination therapy regimen was discovered in detail, paving the way to optimize cancer immunotherapy for enhanced efficacy and decreased side effects. Graphical abstract: Image, graphical abstract